Extremely Preterm Babies-Legal Aspects and Palliative Care at the Border of Viability - Reinhard Dettmeyer (MDPI AG, 2022)
There are various legal considerations and rare decisions of courts in western countries concerning palliative care and the border of viability in cases of extremely preterm babies. Nevertheless, on the one hand, regulations and decisions of courts describe the conditions physicians have to accept. On the other hand, courts are also able to accept that every case can be special, and needs a unique answer. Therefore, the framework can be described as well as the medical disciplines, which should be involved in a particular case.